2014
DOI: 10.5198/jtlu.v7i3.485
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with travel and residential self-selection: How do preferences moderate the impact of the Hiawatha Light Rail Transit line?

Abstract: Abstract:Policies in urban and transportation planning increasingly aim at improving residents' wellbeing. Satisfaction with travel (SWT) is a relevant component of well-being. Insight into the effect of the built environment on SWT is limited and therefore the focus of this paper. To assess this effect, a crucial issue is to what extent a relationship between the built environment and SWT is due to residential self-selection. To explore this question, a survey was held in corridors of the Twin Cities, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 39 publications
8
67
1
Order By: Relevance
“…As a result, the total effects of two socio-demographic variables -age and income -are significantly and positively associated with SWB, as reported in Table 4. This finding is also consistent with previous studies (Cao & Ettema, 2014;Diener & Suh, 1997).…”
Section: Resultssupporting
confidence: 83%
“…As a result, the total effects of two socio-demographic variables -age and income -are significantly and positively associated with SWB, as reported in Table 4. This finding is also consistent with previous studies (Cao & Ettema, 2014;Diener & Suh, 1997).…”
Section: Resultssupporting
confidence: 83%
“…For example, Silva (2014) describes the overall conclusions reached on RSS as 'mixed' with earlier studies tending to conclude that RSS is more influential than land-use factors (Kitamura et al, 1997) while more recent studies suggest that the opposite is the case (Bhat and Guo, 2007). Based on the extensive review of empirical results by Cao et al (2009), it appears that while RSS is found to contribute to the influence of the built environment on travel, much research has found an independent effect of the built environment on travel behaviour beyond self-selection (Cao and Ettema, 2014;Silva, 2014).…”
Section: Introductionmentioning
confidence: 66%
“…Furthermore, it is also possible that satisfaction with a particular trip affects travel-liking attitudes, instead of the other way around. Recently, Cao and Ettema (2014) also claimed that people move to locations that allow them to have 'happy travel'. This suggests a reciprocal relationship between the residential location choice and travel satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…According to De Vos et al (2015a) − using the same data as this study − suburban residents experience more positive feelings during travel and evaluate their trip more positively compared to urban residents, and this for all travel modes. Also Cao and Ettema (2014) indicate that travel satisfaction is lower in high-density neighbourhoods compared to lowdensity suburbs, although public transport availability seems to positively affect travel satisfaction. It is not directly clear, however, why travel satisfaction differs according to the residential location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation